Stock Returns Volatility in Nepal: Evidence during Covid-19 - Rana, Surya Bahadur (Butwal Campus Journal, 2022)
This study scrutinizes the stock returns volatility pattern in Nepal during the COVID-19 period from March 3, 2020 to February 27, 2022. By examining GARCH family models with Generalized Error Distribution specification, the results of symmetric GARCH models show that there is persistent volatility in daily stock returns in Nepal over the study period. The observed persistent volatility in daily stock returns indicate that the current shocks in daily stock returns exist in forecasting variance for longer period in future. The results of asymmetric TGARCH (1, 1) model show that there is the leverage effects on the volatility of daily stock returns in Nepal during the study period. The observed leverage effects implies that uncomplimentary news have larger effects on the volatility than the complimentary news of the same intensity. Finally, results establish the GARCH (1, 1) model as the best fitted symmetric model to explain the volatility persistence and the TGARCH (1,1) model as the best fitted asymmetric models to predict the leverage effects on the time varying conditional volatility of daily stock in Nepal. The main implication of findings from this study is that it offers an additional insight to form sound investment strategy to address risk structure of Nepali stock market.